(untitled) (Voice of Teacher, 2022)
The present paper argues that globalization has created diasporas subjects among immigrants communities as they go through a number of adjustment in the host culture. As recorded by Bharati Mukherjee in her story collection Middleman and Other Stories the protagonists have to constantly adopt and adapt new forms of hybridity in the US. With an advent of globalization, people started migrating into first world in search of better opportunities and social security, but the cultural differences always played a role in determining their identities. In other words, globalization opened the space for multiculturalism, and multiculturalism, in turn, bore diasporic subjects. This immigrants thus lived with an identity that they can’t claim to be their own. They always struggle, constantly adopting and adapting a newer and newer form of identity negotiated heavily in a cross cultural setting.